The country and Irish problem. Issue 3 (December 2020) - Erraught, Stan
Abstract: Country music has been popular in Ireland since the 1960s, most notably in the work of homegrown performers. Despite the durability of this appeal in the face of huge changes in Ireland and in the Irish music industry over a half-century, it remains curiously underexamined in the literature on Irish popular music. In this paper, I wish to argue the following: (1) Country music did not simply arise 'naturally' in Ireland as a reflection of musical or national characteristics: it was promoted as such. (2) Both popular and academic literature on the subject have tended to unreflectively echo the narrative that was introduced alongside the music in order to fix its audience. (3) In so doing, the literature reproduces a set of anxieties about modernity as it arrived in Ireland, about the postcolonial condition and about authenticity, even as it attempts to locate Irish popular music within these concerns.